ANIMALISTIC PAREMIOLOGY IN UZBEK AND ENGLISH LANGUAGE - Makhmudova Shakhinabonu (Scholars Digest Publishing, 2023)
This article discusses the meaning of the term parema and paremiology . In order to conduct a comparative analysis, this article also provides the translation of idioms and idiomatic expressions involving animal names into English and Uzbek. A few idioms' translations into a target language are provided to show how two languages' lexical and semantic characteristics.
Keywords: Paremiology, paremas, proverbs, names of animals, phraseological units, zoonyms.